A model for promoting student participation in school governance. Issue 4 (5th December 2019) - Cheng, Eric C.K.; Leung, Yan Wing; Yuen, Wai Wa; Tang, Hei Hang Hayes
Abstract : Purpose: The purpose of this paper is to highlight the urgent need for a genuinely effective and attainable citizenship education model in Hong Kong's schools, which focusses on promoting student participation in school governance. It is an empirical citizenship education management model for school leaders that illustrates the predictive effects of personally responsible, participatory, justice-oriented and patriotic citizenship, necessarily supported by school management practices, school ethos and teacher beliefs. Design/methodology/approach: A total of 3, 209 students from 51 secondary schools in Hong Kong participated in a quasi-experimental design questionnaire survey. A structural equation model (SEM) was applied to confirm the model. Findings: The results of the SEM show that the values and cultural practices held by a school's teachers drive the implementation of its citizenship education. Moreover, it is well known that organizational values can exert a powerful influence and it is the same within educational structures: management practices in schools have an impact on ethos, teachers' beliefs and student participation in school governance. Practical implications: The paper provides practical proposals for school leaders to create opportunities for student participation in school governance. Originality/value: This study builds on existing literature and provides school leaders with a practical model for implementing student participation in school governance.